Risk of hyperkalemia from renin–angiotensin–aldosterone system inhibitors and factors associated with treatment discontinuities in a real-world population. Issue 5 (17th December 2019) - Wetmore, James B; Yan, Heng; Horne, Laura; Peng, Yi; Gilbertson, David T
Abstract: Background: Hyperkalemia rates in renin–angiotensin–aldosterone system (RAAS) inhibitor users, and factors associated with treatment interruptions and cessations, have not been explored in a large, population-wide database. Methods: RAAS inhibitor users were identified in the linked UK Clinical Practice Research Datalink-Hospital Episodes Statistics data set, 2009–15. Treatment interruptions (no active prescription followed by reappearance) and cessations were determined. Hyperkalemia (serum K + >5.5 mmol/L) rates were calculated and factors associated with interruptions and cessations modeled using time-varying Cox regression, including hyperkalemia (as a time-dependent variable). Results: Among 434 027 RAAS inhibitor users, the hyperkalemia rate was 1.30 (95% confidence interval 1.28–1.32) per 100 patient-years. Of 73.7% of patients who experienced off-treatment periods, 57.6% experienced interruption only, 7.5% cessation only and 8.6% both. Within 1 year of initiating RAAS inhibitor treatment, approximately one-third of the patients experienced interruption or cessation. Hazard ratios for patients with severe hyperkalemia were 1.10 (10.5–1.16) for interruptions and 3.37 (3.25–3.50) for cessation. Compared with no chronic kidney disease (CKD), risk of interruption was 1.20 (1.16–1.25) and 1.57 (1.44–1.72) for Stages 4 and 5, respectively, and of cessation was 2.20 (2.07–2.33) and 2.87 (2.56–3.22). Risk of interruption increased for patients with heart failure or diabetes [1.04 (1.02–1.05); 1.13 (1.12–1.14), respectively] but the risk of cessation decreased [0.85 (0.82–0.87); 0.92 (0.90–0.94)]. Conclusions: Risk of RAAS inhibitor interruption and cessation increased as CKD stage progressed. Efforts targeting reasons for interruptions and, especially, cessations, such as hyperkalemia prevention, could decrease off-treatment periods for patients who would otherwise benefit, such as those with CKD, heart failure or diabetes.